2006
DOI: 10.1007/s11240-006-9102-6
|View full text |Cite
|
Sign up to set email alerts
|

Differential organ infection studies, potyvirus elimination, and field performance of virus-free garlic plants produced by tissue culture

Abstract: Presence of potyvirus in single garlic (Allium sativum L.) cloves from the same bulb, and in five single leaves excised from commercial fieldgrown individual plants was studied using ELISA. It was found that the viruses were not present in all organs of the same plant, since some cloves of the same bulb were infected with potyvirus but some others were potyvirus-free. Analyzed leaves from a given plant also exhibited irregular distribution of potyvirus. This study also aimed to obtain potyvirusfree plants from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 18 publications
5
20
0
5
Order By: Relevance
“…In fact, the principal target of antiviral activity of these molecules is the inosine monophosphate dehydrogenase, an enzyme that catalyzes the conversion of inosine 5'-monophosphate (IMP) in xantosine 5'-monophosphate and is able to alter the pathway for the production of guanosine mono-di-and triphosphate. The presence of its inhibitor acts on this Weiland et al, 2004;Panattoni et al, 2006Panattoni et al, , 2007aSkiada et al, 2009bJames et al, 1997;Cieslinska, & Zawadzka, 1999;Cieslinska, 2002;O'Herlihy et al, 2003Janeckova, 1993Gabova, 1995;Chen & Li, 2001;Chen & Lu, 2000Kolbanova et al, 2004Iwanami & Ieki, 1994Cieslinska, 2003Conrad, 1991Green et al, 1992;Park et al, 1994;Kim et al, 1996;Truskinov & Rogozina, 1997;Faccioli & Zoffoli, 1998;Horackova, 1998;Nascimento et al, 2003;Fang et al, 2005Loi et al, 1991Schulze & Kluge, 1994Kim et al, 1994Xu & Niimi, 1999;Xu et al, 2000Ram et al, 2005Bertaccini et al, 2004Ramírez-Malagón et al, 2006Xu et al, 2004Lim et al, 1993;Toussaint et al, 1993;Fletcher et al, 1998;Freitas & Rezende, 1998;Yap et al, 1999;Fletcher & Fletcher, 200...…”
Section: Mechanism Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the principal target of antiviral activity of these molecules is the inosine monophosphate dehydrogenase, an enzyme that catalyzes the conversion of inosine 5'-monophosphate (IMP) in xantosine 5'-monophosphate and is able to alter the pathway for the production of guanosine mono-di-and triphosphate. The presence of its inhibitor acts on this Weiland et al, 2004;Panattoni et al, 2006Panattoni et al, , 2007aSkiada et al, 2009bJames et al, 1997;Cieslinska, & Zawadzka, 1999;Cieslinska, 2002;O'Herlihy et al, 2003Janeckova, 1993Gabova, 1995;Chen & Li, 2001;Chen & Lu, 2000Kolbanova et al, 2004Iwanami & Ieki, 1994Cieslinska, 2003Conrad, 1991Green et al, 1992;Park et al, 1994;Kim et al, 1996;Truskinov & Rogozina, 1997;Faccioli & Zoffoli, 1998;Horackova, 1998;Nascimento et al, 2003;Fang et al, 2005Loi et al, 1991Schulze & Kluge, 1994Kim et al, 1994Xu & Niimi, 1999;Xu et al, 2000Ram et al, 2005Bertaccini et al, 2004Ramírez-Malagón et al, 2006Xu et al, 2004Lim et al, 1993;Toussaint et al, 1993;Fletcher et al, 1998;Freitas & Rezende, 1998;Yap et al, 1999;Fletcher & Fletcher, 200...…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Thermotherapy, even in association with other techniques such as tissue culture, represents the most fre- Goussard & Wiid, 1992;Popescu et al, 2003Popescu et al, , 2010Gambino et al, 2006Gambino et al, , 2010Gribaudo et al, 2006;Borroto-Fernández et al, 2009;Youssef et al, 2009Ramos & Zamora, 1999D'Onghia et al, 2001;Golino et al, 2007;Quainoo et al, 2008Fitch et al, 2001Parmessur et al, 2002;Ramgareeb et al, 2010Ebi et al, 2000Ayabe & Sumi, 2001;Ramírez-Malagón et al, 2006Truskinov & Rogozina, 1997Mahmoud et al, 2009Wangai & Bock, 1996Morris et al, 1997;S edivá et al, 2006;Kumar et al, 2009;Kabir et al, 2010 quently used technique for sanitation over the last 20 years, while applications of methods such as chemotherapy and tissue culture represent the main topic in plant sanitation research.…”
Section: Comparison Of Techniquesmentioning
confidence: 99%
“…Therefore each type of crop and viral infection should be considered separately. In localization studies performed in garlic tissue, the potyvirus PVY was not detected in shoot meristem (Ramírez‐Malagón et al ., ) suggesting a possible high percentage of success for eradication of RanMMV (also a potyvirus) using SAM; however, no such information is available for the ophiovirus RWMV. Other critical points need to be considered; one of the main difficulties with SAM culture of ranunculus is the high mortality caused by endogenous bacterial contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Torres et al, (2000) recovered 90% plants free of virus from the cloves of garlic cultivar Amarante through dry heat thermotherapy (37 °C for 35 days). However, according to Ramirez et al, (2006) though mericlones produced through thermotherapy were found to be free from viruses, but the overall efficiency of virus elimination was low. Thermotherapy at 30 o C for one week and 36 o C for 4 and 5 weeks in dry chamber followed by stem disc dome culture resulted in 61 and 77% elimination of viruses GarVs and OYDV, respectively (Fahimeh et al, 2014).…”
Section: Thermotherapymentioning
confidence: 99%